Analysis on the condition and function of the “Ba” construction into the Bare-verb - Shi, Shaojie (Journal of Chinese Language and Culture Studies, 2023)
The construction of "Ba" has always been one of the focus of modern Chinese research. This is not only because it is complicated and diverse in structure, but also is closely related to the semantic relationship expressed. This article analysis Bare-verb which can enter “Ba” construction, explore the scenario of the application of the sentence, and think about the teaching practice of the structure for the application scenario. This study divided Bare-verb into single syllables, two-syllables and multi-syllables Bare-verb according to syllables. By analyzing, the single syllables of Bare-verb must have the condition of rhetoric; the two-syllables of bare-verbs must have removal, completion and continuous righteousness. The multi-syllables of Bare-verb appear in the form of "-hua". The conclusion is that this type of Bare-verb will appear in prayer sentences, negative sentences, doubts, and compound sentences, and the sentence pattern has the asymmetric and enhanced language function.